Analysis of World Championship Swimmers Using a Performance Progression Model - Yustres, Inmaculada; del Cerro, Jesús Santos; González-Mohíno, Fernando; Peyrebrune, Michael; González-Ravé, José María (Frontiers in Psychology, 2020)
Purpose: The aim of this study was to create a performance progression model of elite competitors in the World Swimming Championships from 2006 to 2017 for all strokes and distances. Secondly, the study aims to identify the ages of peak performance, the annual ratios of progression and the effect of junior status in determining senior success. Methods: Data were obtained from FINA regarding the participants of junior and senior World Championships (WCs) between 2006 and 2017. The final filtered database included 4076 swimmers after removing those who only participated in the junior WCs. Statistical models were used to examine differences between the top senior swimmers (the top 30% best performances; T30) and lower level swimmers (the bottom 70% performances; L70) for minimum age (MA), progress (P) and best junior time (BJ). In order to identify the variables that contribute to reach the T30 group, a logistic regression (LR), stepwise LR and decision tree were applied. To analyze the effect of each variable separately, a simple LR (gross odds ratio) was performed. Ratio probabilities (OR) and 95% confidence intervals were calculated for each variable. Results: Swimmer’s BJ and P were higher in the T30 group (p <0.000). The decision tree showed the greatest explanatory capacity for BJ, followed by P. The MA had a very low explanatory capacity and was not significant in the LR. Conclusion: Swimmers with exceptional junior performance times, or have a high rate of progress are more likely to be successful in senior competitions.